(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
Based on the nature exploration and hydrogeological calculations on the subsurface water deposits located in the south part of Trinidad City and Caribbean Sea (Republic of Cuba), it has been chosen an exploitation section of sweet sub-surface waters. On this section with the chosen scheme of distribution of water-proof buildings (boreholes), it is possible to pump out more quantities of needed water (100 L per second) for the Trinidad City and the tourist center located near the city. By the way according to the mentioned calculations the mineralization of the pumped out water during the exploitation period (30 years) will remain in allowed limits.